The Influence of Service Quality and Islamic Branding on Customer Loyalty: The Role of Consumer Trust Moderation in The Context of Islamic Business - Afriana Dania; Maksum (Universitas Airlangga, 2026)
This study examines the influence of service quality and Islamic branding on customer loyalty, with consumer trust acting both as an independent variable and as a moderating variable in the context of Islamic fashion retail. Increasing competition in the Muslim fashion industry requires businesses not only to provide quality products but also to strengthen service performance, maintain credible Islamic branding, and build consumer trust to sustain long-term customer relationships. This research was conducted at Queen Hijab Store, a retail business specializing in modest fashion products targeting Muslim consumers. A quantitative research approach was applied using a survey method. Data were collected from customers of Queen Hijab Store through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The analysis aimed to examine the relationships among service quality, Islamic branding, consumer trust, and customer loyalty, as well as to evaluate the moderating role of consumer trust. The findings indicate that service quality and consumer trust play important roles in shaping customer loyalty. High service performance encourages repeat purchases and strengthens long-term relationships with customers. Consumer trust also enhances the influence of Islamic branding on loyalty, while Islamic branding alone is not sufficient to directly create strong customer loyalty. These results highlight the importance of integrating service excellence, credible Islamic values, and trustworthy business practices to maintain sustainable customer loyalty in the Islamic fashion retail industry.